Temporal evolution of changes in left ventricular function induced by cold pressor stimulation. An assessment with radionuclide angiography and gold 195m. Issue 5 (May 1984) - Dymond, D S; Caplin, J L; Flatman, W; Burnett, P; Banim, S; Spurrell, R
Abstract : The evolutionary changes in left ventricular function induced by cold pressor stimulation were investigated at 90 second intervals by rapid sequential first pass radionuclide angiography using the short half life tracer gold 195m. The results in 12 subjects with normal coronary arteries were compared with those in 12 patients with coronary artery disease. Left ventricular ejection fraction fell significantly from resting values in both groups after 1 minute of cold pressor, but only in patients with coronary disease was the significant fall maintained at 2.5 and 4 minutes. In both groups, the maximum decrease in ejection fraction occurred after 1 minute, whereas the maximum rise in systolic blood pressure occurred after 2.5 minutes. New abnormalities of regional ventricular function developed in 10 normal subjects after 1 minute of cold, with a total of 12 new abnormal segments. Only two such segments were seen at the later stages of imaging. Twenty one new segments developed after 1 minute in the coronary disease group, and 13 segments remained abnormal after 4 minutes. Three patients, two of whom had left main stem stenoses, showed persistent abnormalities of ventricular function after 2 minutes of recovery from cold stimulation. Thus left ventricular function changes rapidly during a period of cold stimulation in both those without and those with coronary disease. When the cold pressor test is used with multiple gated equilibrium imaging, the timing of imaging may be crucial to the results and interpretation of the test. The discordance between functional changes and rise in blood pressure is further evidence that alterations in afterload are not solely responsible for cold induced abnormalities.